Brainstorming Technologies Based on A Communicative-Creative Approach - Xalikov To’lqin Xurramovich (European International Journal of Multidisciplinary Research and Management Studies, 2025)
An important part of any team’s success is the ability to brainstorm effectively. Brainstorming encourages creativity and innovation, which are very important when tackling business challenges and identifying opportunities. But while many teams hold brainstorming sessions, not all are equally effective. If you feel your sessions are falling short, we’re here to help. This article will guide you on how to create productive brainstorming sessions through different techniques and practical tips.